The Problem Of Meaning In Literary Translation - Safia Boushaba (Al-Lisaniyyat, 2004)
This paper deals with the interpretation of the meaning of the source language text (SLT) in literary translation taking into con-sideration the relationship of the SLT with the author’s personal experience and his way of conceptualising things. The author’s intention in a literary text cannot be determined easily and might be interpreted subjectively by the translator. Some examples taken from Sarwat Okasha and Antonius Bashir’s translations of Gibran’s The Prophet, show how these two translators could have avoided a subjective translation of the concepts of « love » and « God » if they took into consideration Gibran’s concept of love and God which govern the meaning of The Prophet. This paper is an attempt to show how translators fail to achieve objective rendition of es-sential concepts in the SLT because of their neglect of the relation-ship that exists between the author’s concept and vision of the world and the meaning of SLT.